2015
DOI: 10.1097/fbp.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Modeling autism-relevant behavioral phenotypes in rats and mice

Abstract: Autism spectrum disorders (ASD) are among the most severe developmental psychiatric disorders known today, characterized by impairments in communication and social interaction and stereotyped behaviors. However, no specific treatments for ASD are as yet available. By enabling selective genetic, neural, and pharmacological manipulations, animal studies are essential in ASD research. They make it possible to dissect the role of genetic and environmental factors in the pathogenesis of the disease, circumventing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 241 publications
(352 reference statements)
1
58
0
Order By: Relevance
“…Consistent with this possibility, at infancy, male but not female pups prenatally exposed to VPA showed communicative deficits, since they emitted less USVs than control pups when isolated from the dam and siblings. In rodents, these USVs play a fundamental role in mother–offspring interactions, as they induce maternal retrieval and elicit care‐giving behaviours in the dam (Servadio et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with this possibility, at infancy, male but not female pups prenatally exposed to VPA showed communicative deficits, since they emitted less USVs than control pups when isolated from the dam and siblings. In rodents, these USVs play a fundamental role in mother–offspring interactions, as they induce maternal retrieval and elicit care‐giving behaviours in the dam (Servadio et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Based on thsee clinical observations, prenatal VPA exposure in rodents is a widely used environmental preclinical model of ASD with face and construct validity (Williams et al ., ; Schneider and Przewlocki, ; Wagner et al ., ; Roullet et al ., ; Sabers et al ., ; Servadio et al ., , ). This model, however, has been mainly validated and used in male rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also differ from studies on Fmr1 knock-out mice and rats, a model for fragile X syndrome. With respect to the ABR, fragile X mice show smaller wave I and III peak amplitudes and no latency differences (Rotschafer et al, 2015). Behaviorally, Fmr1 knock-out rats show typical startle responses and no significant PPI differences.…”
Section: Comparison With Other Animal Models Of Autismmentioning
confidence: 92%
“…prepulse stimulus (10 ms white noise at either 75 dB SPL or 85 dB SPL; 5 ms rise/fall time). During a continuous background noise (60 dB SPL white noise), prepulses were presented 30 or 100 ms (i.e., the interstimulus interval, ISI) before the startle stimulus for maximum PPI (Ison et al, 1973;Graham, 1975;Graham and Murray, 1977;Hoffman and Ison, 1980;Valsamis and Schmid, 2011;Typlt et al, 2013;Pinnock et al, 2015;Zaman et al, 2017). In total, the animals were randomly presented 10 trials of each stimulus type (startle alone; 75 dB at 30 ms ISI; 75 dB at 100 ms ISI, 85 dB at 30 ms ISI, and 85 dB at 100 ms ISI), with the trials separated by a randomly varying ITIs (12, 15 or 18 s; see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Animal models are increasingly utilized to investigate the intricate processes and mechanisms underlying ASD behaviors and phenotypes, and they are necessary for any kind of drug or therapeutic testing [71]. Both rodent and non-human primate models of maternal immune activation (MIA) have shown that even in the absence of overt infection, activation of the maternal immune system using viral and bacterial mimics as well as the cytokine IL-6 can result in behavioral changes in the offspring [7274].…”
Section: Future Directionsmentioning
confidence: 99%